Use of amorphous-poly-alpha-olefin as an additive to improve terminal blend rubberized asphalt. (20th December 2019) - You, Lingyun; Yan, Kezhen; Wang, Daocheng; Ge, Dongdong; Song, Xiaojin
Highlights: The TB asphalt was modified with different dosage of APAOs. The effect of APAO on the mechanical performance of TB asphalt was evaluated. The addition APAOs improved the performance of TB asphalt in both high- and low-temperature. The application of ESEM in evaluating the micromorphology of asphalt should be further improved. Abstract: Terminal blend rubberized asphalt (TB), a rubber-modified asphalt, exhibits excellent storage stability and compatibility compared with traditional rubber modified asphalt. However, the investigation regarding its performance at high temperatures is not sufficient. In this study, the amorphous-poly-alpha-olefin (APAO) additive was employed as a modifier to improve the performance of the TB asphalt at both high- and low-temperature. Firstly, the general performance and rotational viscosity were tested via conventional tests in the laboratory. Besides, the rheological properties at both high and low temperatures were evaluated by a dynamic shear rheometer (DSR) test and a bending beam rheometer (BBR) test, respectively. Finally, the micromorphology of specimens was detected through an environmental scanning electron microscope (ESEM) test. The experiment results showed that with the increase in APAO content in the TB asphalt, the increasing trend of rotational viscosity and the softening point was noticeable. In addition, the rutting factor ( G* / sinδ ), recovery percentage ( R ), and non-recoverable compliance ( Jnr ) suggested that the APAO modified TB asphalt presented a remarkable rutting resistance at high-temperature. When the content of APAO reached 6% (wt.), the low-temperature crack resistance of asphalt was significantly improved through the results of low-temperature toughness. Meanwhile, the ESEM test results presented that the APAO modifications were evenly distributed in asphalt and formed a dense grid structure, which helped improve the binding force between the components in the polymer modified asphalt.